Effect of tegument integrity on the light sensitivity in seeds of Cucumis anguria L - Chacur, M. M.; Takaki, M. (Inst Tecnologia Parana, 1996)
Cucumis anguria present dark germinating seeds at 25 degrees C. Seeds without the tegument are photosensitive germinating better in darkness than under continuous white light. However, pre-incubation at 40 degrees C for 48 hours allows the seeds to germinate under continuous white light and the incubation of naked seeds at -0.6MPa restored the light inhibition of seed germination. Our results suggest that the tegument interact with the phytochrome in the control of seed germination in part of the population of seed of C. anguria.
Keywords: Cucumis anguria; seed coat; seed germination; phytochrome; light